2022
DOI: 10.1007/s00520-022-07343-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evaluation of supportive care using an electronic health record text-mining tool: G-CSF use in breast cancer patients

Abstract: Purpose Chemotherapy-induced febrile neutropenia (FN) is a life-threatening and chemotherapy dose-limiting adverse event. FN can be prevented with granulocyte-colony stimulating factors (G-CSFs). Guidelines recommend primary G-CSF use for patients receiving either high (> 20%) FN risk (HR) chemotherapy, or intermediate (10–20%) FN risk (IR) chemotherapy if the overall risk with additional patient-related risk factors exceeds 20%. In this study, we applied an EHR text-mining tool for real-world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Previously, we validated a text-mining tool to extract data from EHR for the evaluation of metastatic renal cell carcinoma treatments (mRCCs) and showed that this method is accurate and seven times faster than manual data extraction [ 18 ]. This tool has already been used in other real-world studies, e.g., to review mRCC treatment patterns and outcomes in two hospitals, to review the use of granulocyte-colony stimulating factor and incidence of febrile neutropenia in breast cancer patients [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we validated a text-mining tool to extract data from EHR for the evaluation of metastatic renal cell carcinoma treatments (mRCCs) and showed that this method is accurate and seven times faster than manual data extraction [ 18 ]. This tool has already been used in other real-world studies, e.g., to review mRCC treatment patterns and outcomes in two hospitals, to review the use of granulocyte-colony stimulating factor and incidence of febrile neutropenia in breast cancer patients [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, only transitioning patients with stable disease from originator to biosimilar is not in line with the principle of the biosimilar being similar to the originator. 42,43 Finally, less retransitioning was reported in studies in which patients received adalimumab than in studies of other TNF inhibitors. Adalimumab was the last biosimilar to be introduced in clinical care, which could mean that the introduction of adalimumab biosimilars benefited from knowledge gained from and experience with the introduction of previous biosimilars for clinicians, pharmacists and patients.…”
Section: Discussionmentioning
confidence: 99%
“…For most patients, the loss of effect or the appearance of adverse events in these studies was not clinically verifiable (objectively) by a physician and could be considered as having been subjective. 40,43 This could be attributed to the 'nocebo effect' (i.e., patients' negative expectations that lead to the experience of adverse events or the perception of a decrease in response). 43,44 However, the nocebo effect is difficult to confirm.…”
Section: Retransitioningmentioning
confidence: 99%
See 2 more Smart Citations